Bee communities along a prairie restoration chronosequence: similar abundance and diversity, distinct composition. Issue 3 (13th March 2017) - Tonietto, Rebecca K.; Ascher, John S.; Larkin, Daniel J.
Abstract: Recognition of the importance of bee conservation has grown in response to declines of managed honey bees and some wild bee species. Habitat loss has been implicated as a leading cause of declines, suggesting that ecological restoration is likely to play an increasing role in bee conservation efforts. In the midwestern United States, restoration of tallgrass prairie has traditionally targeted plant community objectives without explicit consideration for bees. However, restoration of prairie vegetation is likely to provide ancillary benefits to bees through increased foraging and nesting resources. We investigated community assembly of bees across a chronosequence of restored eastern tallgrass prairies and compared patterns to those in control and reference habitats (old fields and prairie remnants, respectively). We collected bees for 3 yr and measured diversity and abundance of in‐bloom flowering plants, vegetation structure, ground cover, and surrounding land use as predictors of bee abundance and bee taxonomic and functional diversity. We found that site‐level variables, but not site type or restoration age, were significant predictors of bee abundance (bloom diversity, P  =   0.004; bare ground cover, P  =   0.02) and bee diversity (bloom diversity, P  =   0.01). There were significant correlations between overall composition of bee and blooming plant communities (Mantel test, P  =   0.002), and both plant and bee assemblages in restorations were intermediate between those of old fields and remnant prairies. Restorations exhibited high bee beta diversity, i.e., restored sites' bee assemblages were taxonomically and functionally differentiated from each other. This pattern was strong in younger restorations (<20 yr old), but absent from older restorations (>20 yr), suggesting restored prairie bee communities become more similar to one another and more similar to remnant prairie bee communities over time with the arrival of more species and functional groups of bees. Our results indicate that old fields, restorations, and remnants provide habitat for diverse and abundant bee communities, but continued restoration of old fields will help support and conserve bee communities more similar to reference bee communities characteristic of remnant prairies.